2017
DOI: 10.1186/s12939-017-0657-0
|View full text |Cite
|
Sign up to set email alerts
|

Engaging and staying engaged: a phenomenological study of barriers to equitable access to mental healthcare for people with severe mental disorders in a rural African setting

Abstract: BackgroundIn low-and middle-income countries, integration of mental health into primary care is recommended to reduce the treatment gap. In this study we explored barriers to initial and ongoing engagement of people with severe mental disorders (SMD) in rural Ethiopia after implementing integrated primary mental healthcare services.MethodsA qualitative approach was employed. In-depth interviews were conducted with 50 key informants: service users/caregivers engaged with care (n = 17), non-engagers and their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 53 publications
1
65
0
1
Order By: Relevance
“…The pattern of clinic attendance, which showed repeated engagement and disengagement , may explain the following. In our nested qualitative study, people with SMI reported that they tended to attend when they were unwell and not for maintenance care .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The pattern of clinic attendance, which showed repeated engagement and disengagement , may explain the following. In our nested qualitative study, people with SMI reported that they tended to attend when they were unwell and not for maintenance care .…”
Section: Discussionmentioning
confidence: 93%
“…There was a statistically significant total effect of reduced psychotic symptom severity on level of reported discrimination, with the direct effect close to significance and the indirect effect not statistically significant. In qualitative interviews with community stakeholders during development of the district mental healthcare plan, stigma and discrimination were predicted to reduce when the community witnessed people with SMI show improvement with treatment . Social contact interventions, whereby people gain direct exposure to people with SMI and learn about the treatability of their condition are the most effective means of reducing stigma and discrimination .…”
Section: Discussionmentioning
confidence: 99%
“…PRIME established a multi-sectoral community health advisory board with representatives from key members of the district leadership (security, gender office, women and youth affairs, religious affairs and education), the community and service users and caregivers, and was chaired by the head of the district health office [82]. The CAB met twice a year to oversee and advise PRIME [83].…”
Section: Settingmentioning
confidence: 99%
“…It was found that experiencing adverse effects of past treatment, especially related to medications, plays a role as a barrier against service utilization. Low level of awareness of patients about necessity of persistent care and adverse effects of medications are great challenges which discourage them to receive care and decrease adherence to treatment (56,61). Educating patients about treatment choices and their potential side effects is considered as an effective strategy to solve this problem (23).…”
Section: B-4-treatment-related Barriers B-4-1-treatment Side-effectsmentioning
confidence: 99%
“…Cost of services 17 (13, 19-22, 24, 25, 48, 55, 56, 58, Location, distance and transportation barriers 13 (13, 19-24, 40, 54, 58, 59, 66, 67) Lack of family or social support 8 (19,20,22,55,56,59,63,68) Inappropriate and inflexible services 8 (19,20,56,59,(66)(67)(68)(69) Waiting time/time concerns barriers 7 (19,21,22,54,58,66,68) lack of adequate services 5 (18,23,24,40,68) Insurance-related limitations 4 (18,22,54,55) Separation of services and lack of integration 3 (40, 58,68) Inappropriate…”
Section: Attitudinal Barriersmentioning
confidence: 99%